A method for preparing a lightweight aggregate foamed geopolymer wall material and a method for assessing carbon footprint

CN122878074APending Publication Date: 2026-10-09CHINA MCC17 GRP CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611039866.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-14
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

[0007]固碳效率偏低:缺乏发泡与碳化养护的协同耦合工艺,CO2扩散阻力大、矿化反应不充分,固碳率普遍低于8%,难以实现材料级负碳化;

Benefits of technology

[0041](1)固废高值化协同利用:采用粉煤灰、高炉矿渣、镁质冶金渣三元复合固废胶凝体系,固废利用率100%,实现大宗工业固废协同资源化,降低固废堆存污染,践行“以废治废”理念。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122878074A_ABST
    Figure CN122878074A_ABST
Patent Text Reader

Abstract

The application discloses a preparation method and a carbon footprint evaluation method of a light aggregate foamed geopolymer wall material, and belongs to the technical field of green and low-carbon building materials. Fly ash, slag and magnesium slag are used as main solid waste raw materials, and solid waste-based unfired light aggregate, composite alkali activator, foaming agent and foam stabilizer are compounded, so that the light aggregate foamed geopolymer wall material with light weight, high strength, low thermal conductivity and high carbon fixation rate is prepared through raw material pretreatment, gradient stirring foaming, pouring and pre-curing, foaming-carbonization synergistic carbon fixation curing and natural curing. A full life cycle carbon footprint evaluation model is simultaneously established to accurately calculate carbon emission and carbon fixation benefits in each stage. The application realizes 100% utilization of solid waste, a carbon fixation rate of greater than or equal to 11%, a 28d compressive strength of greater than or equal to 3.8MPa, a thermal conductivity of less than or equal to 0.155W / (m*K), a volume weight of less than or equal to 580kg / m 3 , and a negative net carbon footprint, and is suitable for the fields of fabricated light wallboard, thermal insulation partition wall, roof insulation layer and non-load-bearing filling wall, etc.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the technical field of green and low-carbon building materials and industrial solid waste resource utilization, specifically involving a method for preparing lightweight aggregate foamed geopolymer wall material and a method for assessing its carbon footprint. Background Technology

[0002] Against the backdrop of the promotion of prefabricated buildings, wall materials must simultaneously meet multiple indicators such as lightweight, thermal insulation, low energy consumption, and low carbon emissions. my country generates a massive amount of industrial solid waste annually, with high stockpiles of bulk solid wastes such as fly ash, blast furnace slag, and magnesia metallurgical slag, and limited comprehensive utilization rates. Long-term stockpiling not only occupies land but also easily causes environmental problems such as dust and water pollution. Simultaneously, under the national "dual-carbon" strategy and the large-scale promotion of prefabricated buildings, the construction industry urgently needs new wall materials that are low-carbon, carbon-sequestering, lightweight, high-strength, thermally insulated, durable, and low-cost.

[0003] Foamed geopolymers, as a new type of low-carbon cementitious material, use industrial solid waste as the main raw material. After alkali activation, a three-dimensional network cementitious structure is formed, and then a foaming system is introduced to prepare porous lightweight materials. It has advantages such as high solid waste utilization rate, low energy consumption, good thermal insulation performance, and great carbon sequestration potential. It is considered an ideal material to replace traditional foamed concrete, aerated concrete, and ordinary silicate cement products.

[0004] Current foamed geopolymer technology still has the following key technical shortcomings:

[0005] Poor foaming stability: A single foaming system is prone to foam rupture, collapse, uneven pore size distribution, and high interconnected porosity, resulting in low material strength, high shrinkage rate, high water absorption rate, and insufficient durability.

[0006] Weak aggregate interface bonding: The interface between lightweight aggregate and geopolymer matrix is ​​prone to forming weak areas, which are easy to crack and fall off, reducing the overall mechanical properties and flexural strength of the material.

[0007] Low carbon fixation efficiency: The lack of synergistic coupling process between foaming and carbonization curing results in high CO2 diffusion resistance, insufficient mineralization reaction, and carbon fixation rate generally below 8%, making it difficult to achieve material-level negative carbonization.

[0008] Insufficient performance synergy: It is difficult to simultaneously achieve lightweight (low density), high strength, low thermal conductivity, low drying shrinkage, and high carbon fixation, thus limiting its engineering applicability;

[0009] Lack of carbon accounting system: No carbon footprint assessment model suitable for the entire life cycle of foamed geopolymer materials has been established, making it impossible to accurately quantify the carbon emissions and carbon sequestration benefits of the entire chain of raw materials, preparation, maintenance, transportation, service, and disposal, and making it difficult to support low-carbon certification and carbon emission reduction accounting;

[0010] Poor industrial adaptability: The raw material ratio and process parameters lack systematic optimization, resulting in poor stability, low yield, and high overall cost in large-scale production.

[0011] Therefore, there is an urgent need to develop a method for preparing and assessing the carbon footprint of lightweight aggregate foamed geopolymer wall materials with a reasonable raw material system, stable and controllable foaming, strong interfacial bonding, efficient carbon sequestration, excellent synergistic performance, scientific carbon accounting, and strong industrial adaptability, so as to provide core technical support for the high-value utilization of solid waste and the low-carbon transformation of the construction industry. Summary of the Invention

[0012] The technical problem to be solved by the present invention is to provide a method for preparing lightweight aggregate foamed geopolymer wall material and a method for assessing its carbon footprint in order to solve the problems mentioned in the background art or achieve better technical effects.

[0013] To solve the above-mentioned technical problems, the inventors, through practice and summarization, derived the technical solution of this invention. This invention discloses a method for preparing a lightweight aggregate foamed geopolymer wall material, the steps of which are as follows:

[0014] S1: Grind fly ash, blast furnace slag, and magnesia metallurgical slag separately to a specific surface area of ​​420~550m². 2 / kg, take 35~55 parts fly ash, 25~40 parts blast furnace slag and 12~25 parts magnesia metallurgical slag and mix them evenly to obtain composite solid waste cementitious material; the solid waste-based porous lightweight aggregate is subjected to surface etching, cleaning, drying and pre-wetting treatment.

[0015] S2: Mix liquid water glass, solid sodium hydroxide, and water evenly, and let stand to obtain a composite activating solution; add the remaining water to the composite solid waste coagulant and premix at low speed, then add the composite activating solution and activate and stir at high speed, then add the pretreated solid waste-based porous lightweight aggregate and disperse at medium speed, then add the foam stabilizer and continue stirring at medium speed, and finally slowly add the foaming agent and stir at low speed to foam, controlling the density of the foamed slurry to be 600~1100 kg / m³. 3 ;

[0016] The composite solid waste-based porous lightweight aggregate is added at a concentration of 18-28% of the mass of the composite solid waste cementitious material; the composite activating liquid is added at a concentration of 9-14% of the mass of the composite solid waste cementitious material; the foaming agent is hydrogen peroxide with a mass concentration of 27.5%, and the amount added is 1.8-3.6% of the mass of the composite solid waste cementitious material; the foam stabilizer is sodium dodecyl sulfate, and the amount added is 0.15-0.45% of the mass of the composite solid waste cementitious material; the water-to-material ratio is 0.48-0.62.

[0017] S3: Inject the foamed composite slurry obtained in step S2 into a mold, and after low-frequency vibration treatment, let it stand at room temperature for 2.5~3.5 hours to foam.

[0018] S4: Place the molded blank in an environment with a temperature of 45~55℃ and a relative humidity of ≥92% for 14~22 hours;

[0019] S5: Foaming-carbonization coupled carbonization curing: Place the demolded green body in a sealed carbonization curing box and cure it for 4-10 hours under the conditions of CO2 concentration of 15~22 vol%, temperature of 30~42℃ and relative humidity of 65~78%.

[0020] S6: Natural curing: The carbonized and cured green body is placed in a normal temperature natural environment for 28 days to obtain lightweight aggregate foamed geopolymer wall material.

[0021] A method for preparing a lightweight aggregate foamed geopolymer wall material, comprising the following steps:

[0022] S1: Grind fly ash, blast furnace slag, and magnesia metallurgical slag separately to a specific surface area of ​​420~550m². 2 / kg;

[0023] Take 35-55 parts of fly ash, 25-40 parts of blast furnace slag, 7-15 parts of magnesia metallurgical slag, and 5-10 parts of heterogeneous auxiliary solid waste and mix them evenly; or take 35-55 parts of fly ash, 20-30 parts of blast furnace slag, 12-25 parts of magnesia metallurgical slag, and 5-10 parts of heterogeneous auxiliary solid waste and mix them evenly; or take 30-45 parts of fly ash, 25-40 parts of blast furnace slag, 12-25 parts of magnesia metallurgical slag, and 5-10 parts of heterogeneous auxiliary solid waste and mix them evenly to obtain composite solid waste cementitious material; perform surface etching, cleaning, drying, and pre-wetting treatment on the solid waste-based porous lightweight aggregate.

[0024] The heterogeneous auxiliary solid waste is selected from any one of steel slag powder, red mud, and recycled silica-alumina powder from construction waste.

[0025] S2: Mix liquid water glass, solid sodium hydroxide, and water evenly, and let stand to obtain a composite activating solution; add the remaining water to the composite solid waste coagulant and premix at low speed, then add the composite activating solution and activate and stir at high speed, then add the pretreated solid waste-based porous lightweight aggregate and disperse at medium speed, then add the foam stabilizer and continue stirring at medium speed, and finally slowly add the foaming agent and stir at low speed to foam, controlling the density of the foamed slurry to be 600~1100 kg / m³. 3 ;

[0026] The composite solid waste-based porous lightweight aggregate is added at a concentration of 18-28% of the mass of the composite solid waste cementitious material; the composite activating liquid is added at a concentration of 9-14% of the mass of the composite solid waste cementitious material; the foaming agent is hydrogen peroxide with a mass concentration of 27.5%, and the amount added is 1.8-3.6% of the mass of the composite solid waste cementitious material; the foam stabilizer is sodium dodecyl sulfate, and the amount added is 0.15-0.45% of the mass of the composite solid waste cementitious material; the water-to-material ratio is 0.48-0.62.

[0027] S3: Inject the foamed composite slurry obtained in step S2 into a mold, and after low-frequency vibration treatment, let it stand at room temperature for 2.5~3.5 hours to foam.

[0028] S4: Place the molded blank in an environment with a temperature of 45~55℃ and a relative humidity of ≥92% for 14~22 hours;

[0029] S5: Foaming-carbonization coupled carbonization curing: Place the demolded green body in a sealed carbonization curing box and cure it for 4-10 hours under the conditions of CO2 concentration of 15~22 vol%, temperature of 30~42℃ and relative humidity of 65~78%.

[0030] S6: Natural curing: The carbonized and cured green body is placed in a normal temperature natural environment for 28 days to obtain lightweight aggregate foamed geopolymer wall material.

[0031] Furthermore, in step S1, the solid waste-based porous lightweight aggregate is prepared by molding and non-firing curing from recycled construction waste powder, slag, and a small amount of fly ash. Its particle size is 3~6mm, cylinder compressive strength is ≥1.8MPa, and water absorption rate is ≤15%.

[0032] Further, in step S1, the surface etching is mechanical etching with an etching depth of 0.2~0.5mm; the drying temperature is 80~100℃ and the drying time is 2~3h; the pre-wetting treatment is performed until the moisture content of the lightweight aggregate is 5~8%.

[0033] Furthermore, the alkalinity coefficient of the composite activating liquid, i.e., the SiO2 / Na2O molar ratio, is 1.1~1.7; and the modulus of the liquid water glass is 2.2~2.6.

[0034] Further, in step S2, the stirring rate during the preparation of the composite activation liquid is 300-500 r / min, the stirring time is 2-5 min, and the standing time is 6-12 min; the premixing stirring rate is 100-200 r / min, and the time is 1-2 min; the high-speed activation stirring rate is 900-1100 r / min, and the time is 4-7 min, where strong shearing synergistically destroys the aluminosilicate network with alkali activation, generating an active aluminosilicate gel phase; the medium-speed stirring rate is 450-600 r / min, and the time is 2-3 min, where the hydroxyl groups on the aggregate surface undergo a condensation reaction with the matrix gel, forming a stable chemical bonding interface; the medium-speed stirring time after adding the foam stabilizer is 1-3 min; and the low-speed foaming stirring rate is 120-180 r / min, and the time is 0.8-1.8 min.

[0035] Furthermore, in step S3, the frequency of the low-frequency vibration is 20~30Hz, the vibration time is 15~25s, and the ambient temperature is 20±5℃.

[0036] Furthermore, the lightweight aggregate foamed geopolymer wall material prepared by any of the above-described methods is a lightweight aggregate foamed geopolymer wall material.

[0037] Furthermore, the lightweight aggregate foamed geopolymer wall material is used in prefabricated lightweight wall panels, thermal insulation partitions, roof insulation layers, or non-load-bearing infill walls.

[0038] Furthermore, a method for assessing the life-cycle carbon footprint of the lightweight aggregate foamed geopolymer wall material includes: defining the life-cycle assessment boundary, constructing a carbon emission factor database, calculating carbon emissions in stages, calculating the net carbon footprint, and optimizing raw material ratios and process parameters in reverse.

[0039] In carbon footprint assessment, the functional unit is 1m. 3 Wall materials assessment covers the entire lifecycle, including raw materials, preparation, transportation, construction, service, and waste recycling.

[0040] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0041] (1) High-value co-utilization of solid waste: The three-element composite solid waste cementing system of fly ash, blast furnace slag and magnesia metallurgical slag is adopted, with a solid waste utilization rate of 100%, realizing the co-utilization of bulk industrial solid waste, reducing solid waste storage pollution, and practicing the concept of "treating waste with waste".

[0042] (2) Lightweight aggregate interface enhancement and stability: Mechanical etching and pre-wetting treatment on the surface of lightweight aggregate significantly improves the bonding strength of the aggregate-matrix interface, reduces microcracks at the interface, and enhances the overall mechanical properties and durability of the material.

[0043] (3) Gradient stirring foaming is stable and controllable: The gradient speed stirring process produces uniform and fine foam with concentrated pore size distribution and fewer interconnected pores, effectively solving problems such as foam collapse, low strength and large shrinkage.

[0044] (4) High-efficiency carbon fixation through foaming-carbonization coupling: The foamed porous structure provides a channel for CO2 diffusion, and carbonization maintenance promotes the active calcium and magnesium mineralization reaction. The carbon fixation rate is ≥11%, and the material achieves negative carbonization, which helps to achieve the "dual carbon" goal.

[0045] (5) Excellent synergistic performance: Lightweight, high strength, low thermal conductivity, low drying shrinkage, and high carbon fixation synergistically; 28-day compressive strength ≥3.8MPa, thermal conductivity ≤0.155W / (m·K), and bulk density ≤580kg / m³. 3 It is suitable for prefabricated wall engineering applications.

[0046] (6) Scientific and practical carbon footprint assessment: Construct a full life cycle carbon footprint assessment model to accurately quantify carbon emissions and carbon sequestration benefits, realize quantifiable, traceable and optimizable carbon data, and support low-carbon certification and carbon emission reduction accounting.

[0047] (7) Significant cost and industrialization advantages: industrial solid waste replaces cement, the amount of alkali activator is optimized, and the cost is reduced by ≥5.5%; the process parameters are stable, the equipment is universal, the operation is simple, it is suitable for large-scale production lines, the yield is high, and the industrialization promotion value is great. Attached Figure Description

[0048] Figure 1 This is a flow chart of the preparation process of the lightweight aggregate foamed geopolymer wall material of the present invention;

[0049] Figure 2 This is a SEM image of the microporous structure of the aggregate-matrix interface of the material of this invention.

[0050] Figure 3 This is a diagram showing the boundary and data flow for calculating the carbon footprint of the material throughout its entire life cycle in this invention. Detailed Implementation

[0051] To make the above-mentioned objectives, features and advantages of the present invention more apparent and understandable, the specific embodiments of the present invention will be described in detail below with reference to specific examples.

[0052] Unless otherwise specified, all raw materials or reagents used in the following examples are commercially available products.

[0053] The fly ash is Grade I or Grade II low-calcium fly ash with a loss on ignition ≤8%; the blast furnace slag is S95 grade granulated blast furnace slag powder with a specific surface area ≥400 m². 2 / kg; Magnesium metallurgical slag is industrial waste residue from magnesium smelting, with a total CaO+MgO content ≥28%;

[0054] Solid waste-based porous lightweight aggregate: It is made by composite molding of recycled stone powder and magnesium slag from construction waste, with only a small amount of fly ash added, which is different from the ternary ratio of cementitious materials; the particle size is 3~6mm; the compressive strength is ≥1.8MPa and the water absorption rate is ≤15%; it is prepared by molding, non-fired curing and micro powder of recycled construction waste, magnesium slag and a small amount of fly ash, forming a differentiated configuration with the raw material system of cementitious materials;

[0055] Composite alkaline activator: composed of liquid water glass (modulus 2.2~2.6) and solid sodium hydroxide (purity ≥96%), with an alkalinity coefficient (SiO2 / Na2O molar ratio) of 1.1~1.7;

[0056] Foaming agent: 27.5% hydrogen peroxide (mass concentration);

[0057] Foam stabilizer: Sodium dodecyl sulfate (SDS);

[0058] A lightweight aggregate foamed geopolymer wall material includes composite solid waste cementitious material, solid waste-based porous lightweight aggregate, composite alkali activator, composite foaming agent and water;

[0059] The composite solid waste gelling material is based on ternary primary solid waste, comprising, by weight: 35-55 parts fly ash, 25-40 parts blast furnace slag, and 12-25 parts magnesia metallurgical slag; optional heterogeneous auxiliary solid waste (one of which can be selected to replace 5-10 parts of the primary solid waste to avoid raw material homogenization): steel slag powder, red mud, and recycled silica-alumina powder from construction waste; the auxiliary solid waste has a free calcium oxide content of ≤3% in steel slag and an alumina content of ≥22% in red mud.

[0060] The dosage of solid waste-based porous lightweight aggregate is 18-28% of the mass of composite solid waste cementitious material;

[0061] The dosage of the composite alkali activator is 9-14% of the mass of the composite solid waste coagulant;

[0062] The amount of hydrogen peroxide added, with a foaming agent concentration of 27.5%, is 1.8~3.6% of the mass of the composite solid waste gelling agent.

[0063] The dosage of the foam stabilizer sodium dodecyl sulfate (SDS) is 0.15~0.45% of the mass of the composite solid waste gelatin.

[0064] The dosage of carbonization catalyst additive is 0.03~0.08% of the mass of composite solid waste coagulant;

[0065] The water used is tap water or industrial purified water, and the water-to-material ratio (water / composite solid waste coagulant) is 0.48~0.62.

[0066] A method for preparing a lightweight aggregate foamed geopolymer wall material, such as Figure 1 As shown, the steps are as follows:

[0067] S1: Raw material pretreatment

[0068] Pretreatment of composite solid waste cementitious material: Fly ash, blast furnace slag, and magnesia metallurgical slag are ground separately in a ball mill to control the specific surface area to 420~550m². 2 / kg, pass through a 75μm square hole sieve to remove coarse particle impurities; mix evenly according to the formula, seal and set aside for later use;

[0069] Pretreatment of lightweight aggregate based on solid waste: The surface of lightweight aggregate is mechanically etched + high pressure water washing + low temperature drying + pre-wetting treatment. The etching depth is 0.2~0.5mm, the drying temperature is 80~100℃ and the time is 2~3h. The pre-wetting is carried out to a moisture content of 5~8%, which improves the interfacial bonding strength between aggregate and geopolymer matrix and reduces interfacial microcracks.

[0070] S2: Preparation of composite slurry

[0071] Preparation of composite activating solution: Add liquid water glass, solid sodium hydroxide and part of water to a stirring tank according to the ratio. Stir at a rate of 300~500 r / min for 2~5 min at room temperature. After mixing evenly, let stand for 6~12 min to eliminate bubbles and stabilize alkalinity.

[0072] Premixing of cementitious material: Add the remaining water to the composite solid waste cementitious material and stir at a low speed of 100~200r / min for 1~2min to fully disperse and initially wet the cementitious material;

[0073] High-speed activation reaction: Add composite activation liquid to the premix and stir at 900~1100 r / min for 4~7 min. Strong shearing action synergistically destroys the aluminosilicate network with alkali activation to generate an active aluminosilicate gel phase.

[0074] Lightweight aggregate dispersion and compounding: pretreated solid waste-based lightweight aggregate is added to the activated slurry and stirred at a medium speed of 450~600r / min for 2~3min. The hydroxyl groups on the surface of the aggregate undergo a condensation reaction with the matrix gel to form a stable chemical bonding interface.

[0075] Foam stabilization and dispersion: Add sodium dodecyl sulfate foam stabilizer and stir at a medium speed of 450~600r / min for 1~3min to make the foam stabilizer evenly dissolved and dispersed, reduce surface tension, and provide a stable foundation for subsequent foaming;

[0076] Low-speed foaming molding: Slowly add hydrogen peroxide foaming agent + trace amount of calcium acetate catalyst, and stir at a low speed of 120~180 r / min for 0.8~1.8 min to avoid foam rupture caused by high shear; control the density of the foamed slurry to 600~1100 kg / m³. 3 This ensures that the foam is uniform, has small pore size, and has few interconnected pores.

[0077] S3: Casting and Static Foaming

[0078] Mold pretreatment: Select steel or plastic molds, and evenly coat the inner wall with water-based release agent with a coating thickness of 0.1~0.2mm to facilitate demolding later;

[0079] Casting and molding: The prepared foamed composite slurry is quickly and evenly injected into the mold to avoid slurry stratification or air bubble residue; after casting, it is placed on a vibration table and vibrated at a low frequency (20~30Hz) for 15~25s to eliminate large air bubbles inside the slurry and improve structural uniformity.

[0080] Room temperature standing foaming: Place the molded blank in a room temperature (20±5℃) and ventilated environment for 2.5~3.5h to allow the foaming agent to fully decompose and produce gas, complete the initial foaming and shaping, and form a stable and continuous porous structure.

[0081] S4: Pre-curing in hot and humid conditions

[0082] After static foaming, the molded green body is transferred into a constant temperature and humidity curing chamber. The curing temperature is controlled at 45~55℃, the relative humidity is ≥92%, and the curing time is 14~22h. The hot and humid environment promotes the rapid gelation reaction of the geopolymer, enabling the green body to form an initial compressive strength ≥1.2MPa, enhancing the structural stability of the green body, and preventing cracking and deformation during subsequent carbonization curing.

[0083] S5: Foaming-Carbonization Coupled Carbon Fixation Curing

[0084] After the pre-curing meets the standards, the green body is demolded and transferred into a closed carbonization curing box. The curing process parameters are controlled as follows: CO2 concentration 15~22 vol%, curing temperature 30~42℃, relative humidity 65~78%, and curing time 4~10h.

[0085] In a closed, high-concentration CO2 environment, CO2 gas rapidly permeates into the porous structure inside the billet, reacting with the active calcium oxide and magnesium oxide in the geopolymer matrix to generate stable carbonate minerals such as calcium carbonate and magnesium carbonate, thus achieving efficient CO2 mineralization and sequestration. At the same time, the carbonation reaction can further improve the material's density, compressive strength, and volume stability, reduce the drying shrinkage rate, and achieve a carbon fixation rate of ≥11%.

[0086] S6: Natural Maintenance and Finished Product Processing

[0087] After carbonization and curing, the green body is removed from the carbonization box and placed in a normal temperature (20±5℃) and natural humidity environment for continued curing for 28 days. After curing, it is cut, ground, chamfered, and repaired according to project requirements. After passing appearance inspection, dimensional deviation detection, and performance testing, the finished lightweight aggregate foamed geopolymer wall material is obtained and stored for later use. The SEM image of the micropore structure of the aggregate-matrix interface of the material of this invention is shown below. Figure 2 As shown.

[0088] The above-mentioned carbon footprint assessment method for lightweight aggregate foamed polymer wall materials, such as Figure 3 As shown, the steps are as follows:

[0089] S1: Assessment Boundary Delineation

[0090] With 1m 3 Lightweight aggregate foamed geopolymer wall materials are used as functional units, and a "cradle-to-grave" full life cycle assessment boundary is adopted to cover the following stages:

[0091] Raw material stage: collection, transportation, and pretreatment (grinding and screening) of industrial solid waste; production and transportation of alkali activators, foaming agents, and foam stabilizers;

[0092] Preparation stage: slurry mixing, casting and molding, static foaming, moist heat pre-curing, carbonization and carbon fixation curing;

[0093] Transportation phase: Road transportation of raw materials from the place of origin to the production plant, and finished products from the production plant to the construction site;

[0094] Construction phase: On-site hoisting, installation, and assembly;

[0095] Service life: The thermal insulation performance of wall materials during the building's service life, reducing carbon emissions corresponding to lower building heating and cooling energy consumption;

[0096] Waste recycling stage: After the building is demolished, the materials are crushed, screened, recycled, or disposed of in a harmless manner.

[0097] S2: Construction of Carbon Emission Factor Database

[0098] A dedicated database has been established based on the "Standard for Carbon Emission Accounting of Building Materials", the IPCC National Greenhouse Gas Inventory, and measured factors from regional power grids.

[0099] Industrial solid waste (fly ash, slag, magnesium slag, recycled construction waste powder): As industrial by-products, the primary carbon emissions are 0;

[0100] Chemical raw materials: water glass, NaOH, hydrogen peroxide, SDS, and calcium acetate are based on measured carbon emission factors from actual industry production.

[0101] Energy factors: The plant's electricity consumption adopts the regional power grid average carbon emission factor; steam consumption adopts the coal-fired boiler emission factor.

[0102] Transportation factor: 0.18 kg CO2 / (t·km) for diesel truck road transport;

[0103] Carbon fixation factor: Carbonization and mineralization carbon fixation amount = total calcium and magnesium active components of the material × measured carbon fixation rate, which is counted as negative carbon emissions;

[0104] Service Energy Saving Factor: Using building energy consumption simulation software, the carbon emission reduction corresponding to the reduction in energy consumption for heating and cooling throughout the year is calculated based on the thermal conductivity of the materials.

[0105] S3: Life Cycle Carbon Emission Accounting

[0106] Step 1: Phased positive total carbon emission accounting (positive emissions, the value is positive)

[0107] Total carbon emissions (Etotal) = E1 (raw material stage) + E2 (preparation stage) + E3 (transportation stage) + E4 (construction stage) + E5 (waste recycling stage);

[0108] Calculation formulas for each item:

[0109] 1) Carbon emissions E1 during the raw material stage

[0110] E1 = Carbon emissions from chemical raw material production + Carbon emissions from electricity consumption in solid waste pretreatment and grinding + Carbon emissions from road transportation of all raw materials;

[0111] Carbon emissions from chemical raw materials = unit mass factor of each activator / foaming agent / auxiliary agent × 1m 3 Material and raw material consumption;

[0112] Grinding power consumption carbon emissions = total grinding power consumption × power grid carbon emission factor;

[0113] Carbon emissions from transportation = weight of raw materials transported × transportation distance × truck emission factor.

[0114] 2) Carbon emissions E2 during the preparation stage

[0115] E2 = Total electricity consumption carbon emissions of mixing equipment + carbon emissions of steam for wet heat pre-curing + carbon emissions of electricity consumption of carbonization curing fan / CO2 gas supply equipment.

[0116] 3) Carbon emissions during the transportation phase (E3)

[0117] Finished product from factory to construction site: 1m finished product 3 Weight × Transport distance × Carbon emission factor of diesel truck.

[0118] 4) Carbon emissions during the construction phase (E4)

[0119] Diesel consumption of on-site hoisting and cutting machinery × diesel carbon emission factor.

[0120] 5) Carbon emissions during the waste recycling phase (E5)

[0121] Electricity consumption and diesel carbon emissions from dismantling crushing, recycling, and screening equipment.

[0122] Step 2: Calculation of two types of negative carbon deductions (deduction items, values ​​are negative)

[0123] 1) Carbonization, mineralization, and carbon sequestration deduction amount C se q

[0124] C se q=1m 3 Total dry mass of material × Measured carbon fixation rate of material

[0125] This part involves the permanent storage of CO2 in the materials, which fully offsets positive carbon emissions.

[0126] 2) Energy saving and carbon emission reduction deduction amount C during service life save

[0127] Based on the comparison of wall insulation performance with ordinary aerated concrete, the reduction in heating and cooling energy consumption throughout the building's life cycle is calculated, and the CO2 emission reduction is converted into a second carbon offset.

[0128] Step 3: Final formula for calculating net carbon footprint

[0129] Net carbon footprint E net =E total -C se q−C save

[0130] If E net <0 indicates that the material has achieved negative carbonization throughout its entire life cycle, and the absolute value represents the total amount of net CO2 sequestered per cubic meter of material.

[0131] S4: Example of Complete Net Carbon Footprint Calculation

[0132] Example 1 Functional unit: 1m 3 Finished material, density 560 kg / m³ 3

[0133] Positive total carbon emissions E total =28.6kgCO2 / m 3 (The sum of all stages including raw materials, chemicals, grinding, mixing, curing, transportation, construction, and waste disposal);

[0134] Carbonization and carbon sequestration deduction C se q = 560 kg × 13.8% = 77.28 kg CO2 / m³ 3 ;

[0135] Service life insulation, energy saving, carbon emission reduction C save =4.52kgCO2 / m 3 ;

[0136] Net carbon footprint E net =28.6-77.28-4.52=-13.2kg CO2 / m 3 ;

[0137] The results correspond completely to those of Example 1, and each value can be verified and traced through the measured values ​​of raw material usage, equipment energy consumption, and carbon fixation rate.

[0138] Examples 2 and 3 use the exact same calculation process, only replacing the corresponding proportions, carbon fixation rate, and energy consumption parameters to obtain the corresponding -11.5 kg CO2 / m³. 3 -14.1kg CO2 / m 3 result.

[0139] S5: Evaluation Result Analysis and Process Reverse Optimization

[0140] Identification of key emission links: Based on the accounting results, analyze the carbon emission ratio of each stage and identify high carbon emission links (such as the production of alkali activators and energy consumption for carbonization maintenance).

[0141] Process parameter optimization: For key emission links, reverse optimization is carried out on raw material ratio (reducing the dosage of high-carbon activator), process parameters (optimizing carbonization curing temperature and time), and energy utilization (adopting waste heat recovery and energy-saving equipment).

[0142] Carbon benefit quantification: Quantify the improvement in carbon sequestration rate and the reduction in carbon emissions of optimized materials, and output a carbon footprint assessment report;

[0143] Low-carbon certification support: The assessment results can be used for low-carbon product certification of materials, carbon emission reduction accounting of prefabricated buildings, and green building material evaluation.

[0144] Example 1

[0145] A lightweight aggregate foamed geopolymer wall material includes composite solid waste cementitious material, solid waste-based porous lightweight aggregate, composite alkali activator, foaming agent, foam stabilizer and water;

[0146] The composite solid waste cementitious material, by weight, includes: 48 parts fly ash, 32 parts blast furnace slag, and 20 parts magnesia metallurgical slag;

[0147] The particle size of the solid waste-based porous lightweight aggregate is 4 mm, and the dosage is 22% of the mass of the composite solid waste cementitious material.

[0148] The alkalinity coefficient of the composite alkali activator is 1.4, and the dosage is 12% of the mass of the composite solid waste coagulant.

[0149] The amount of hydrogen peroxide added, with a foaming agent concentration of 27.5%, is 2.6% of the mass of the composite solid waste gelling agent.

[0150] The dosage of the foam stabilizer sodium dodecyl sulfate (SDS) is 0.3% of the mass of the composite solid waste coagulant;

[0151] The water is tap water or industrial purified water, and the water-to-material ratio (water / composite solid waste coagulant) is 0.54.

[0152] A method for preparing a lightweight aggregate foamed geopolymer wall material, comprising the following steps:

[0153] S1: Raw material pretreatment

[0154] Pretreatment of composite solid waste cementitious material: Fly ash, blast furnace slag, and magnesia metallurgical slag are ground separately in a ball mill to control the specific surface area to 480 m². 2 / kg, pass through a 75μm square hole sieve to remove coarse particle impurities; mix evenly according to the formula, seal and set aside for later use;

[0155] Pretreatment of lightweight aggregate based on solid waste: The surface of lightweight aggregate is mechanically etched, high-pressure water washing, low-temperature drying and pre-wetting treatment are performed. The etching depth is 0.2~0.5mm, the drying temperature is 90℃ and the time is 2.5h, and the pre-wetting is carried out to a moisture content of 6%, which improves the interfacial bonding strength between aggregate and geopolymer matrix and reduces interfacial microcracks.

[0156] S2: Preparation of composite slurry

[0157] Preparation of composite activating solution: Add liquid water glass, solid sodium hydroxide and part of water to a stirring tank according to the ratio. Stir at a rate of 300~500 r / min for 2~5 min at room temperature. After mixing evenly, let stand for 8 min to eliminate bubbles and stabilize alkalinity.

[0158] Premixing of cementitious material: Add the remaining water to the composite solid waste cementitious material and stir at a low speed of 100~200 r / min for 1.2 min to fully disperse and initially wet the cementitious material;

[0159] High-speed activation reaction: Add composite activation liquid to the premix and stir at 900~1100r / min for 5min. The strong shearing action promotes the dissociation of the aluminosilicate structure on the surface of solid waste particles, forming a uniform, fine and non-agglomerated activated slurry.

[0160] Lightweight aggregate dispersion and compounding: Add pretreated solid waste-based lightweight aggregate to the activated slurry and stir at a medium speed of 450~600r / min for 2.5min to ensure that the lightweight aggregate is evenly dispersed in the slurry and to avoid aggregate settling or agglomeration.

[0161] Foam stabilization and dispersion: Add sodium dodecyl sulfate foam stabilizer and stir at a medium speed of 450~600r / min for 1~3min to make the foam stabilizer evenly dissolved and dispersed, reduce surface tension, and provide a stable foundation for subsequent foaming;

[0162] Low-speed foaming molding: Slowly add hydrogen peroxide foaming agent and stir at a low speed of 120~180 r / min for 1.2 min to avoid high shear causing foam rupture; control the density of the foamed slurry to 560 kg / m³. 3 This ensures that the foam is uniform, has small pore size, and has few interconnected pores.

[0163] S3: Casting and Static Foaming

[0164] Mold pretreatment: Select steel or plastic molds, and evenly coat the inner wall with water-based release agent with a coating thickness of 0.1~0.2mm to facilitate demolding later;

[0165] Casting and molding: The prepared foamed composite slurry is quickly and evenly injected into the mold to avoid slurry stratification or air bubble residue; after casting, it is placed on a vibration table and vibrated at a low frequency (20~30Hz) for 20 seconds to eliminate large air bubbles inside the slurry and improve structural uniformity.

[0166] Room temperature standing foaming: Place the molded blank in a room temperature (20±5℃) and ventilated environment for 3 hours to allow the foaming agent to fully decompose and produce gas, complete the initial foaming and shaping, and form a stable and continuous porous structure.

[0167] S4: Pre-curing in hot and humid conditions

[0168] After static foaming, the molded green body is transferred into a constant temperature and humidity curing chamber, where the curing temperature is controlled at 50℃ and the relative humidity at 95% for 18 hours. The hot and humid environment promotes the rapid gelation reaction of the geopolymer, enabling the green body to form an initial compressive strength ≥1.2MPa, enhancing the structural stability of the green body, and preventing cracking and deformation during subsequent carbonization curing.

[0169] S5: Foaming-Carbonization Coupled Carbon Fixation Curing

[0170] After the pre-curing is completed, the green body is demolded and transferred into a closed carbonization curing box. The curing process parameters are controlled as follows: CO2 concentration 20 vol%, curing temperature 35℃, relative humidity 72%, and curing time 7 hours.

[0171] In a closed, high-concentration CO2 environment, CO2 gas rapidly permeates into the porous structure inside the billet, reacting with the active calcium oxide and magnesium oxide in the geopolymer matrix to generate stable carbonate minerals such as calcium carbonate and magnesium carbonate, thus achieving efficient CO2 mineralization and sequestration. At the same time, the carbonation reaction can further improve the material's density, compressive strength, and volume stability, reduce the drying shrinkage rate, and achieve a carbon fixation rate of ≥11%.

[0172] S6: Natural Maintenance and Finished Product Processing

[0173] After carbonization and curing, the green body is removed from the carbonization box and placed in a normal temperature (20±5℃) and natural humidity environment for continued curing for 28 days. After curing, it is cut, polished, chamfered, and repaired according to project requirements. After passing the appearance inspection, dimensional deviation detection, and performance test, the finished lightweight aggregate foamed geopolymer wall material is obtained and put into storage for later use.

[0174] Carbon footprint assessment of the above-mentioned lightweight aggregate foamed geopolymer wall material: Net carbon footprint -13.2 kg CO2 / m³ 3 .

[0175] Performance test results: 28-day compressive strength 4.4 MPa; thermal conductivity 0.142 W / (m·K); bulk density 560 kg / m³ 3 Carbon fixation rate 13.8%; cost reduction 6.5%; shrinkage rate 0.25%.

[0176] Example 2

[0177] A lightweight aggregate foamed geopolymer wall material includes composite solid waste cementitious material, solid waste-based porous lightweight aggregate, composite alkali activator, foaming agent, foam stabilizer and water;

[0178] The composite solid waste cementitious material, by weight, includes: 42 parts fly ash, 38 parts blast furnace slag and 20 parts magnesia metallurgical slag;

[0179] The particle size of the solid waste-based porous lightweight aggregate is 5 mm, and the dosage is 26% of the mass of the composite solid waste cementitious material.

[0180] The alkalinity coefficient of the composite alkali activator is 1.3, and the dosage is 11% of the mass of the composite solid waste coagulant.

[0181] The amount of hydrogen peroxide added, with a foaming agent concentration of 27.5%, is 2.2% of the mass of the composite solid waste gelling agent.

[0182] The dosage of the foam stabilizer sodium dodecyl sulfate (SDS) is 0.25% of the mass of the composite solid waste coagulant;

[0183] The water is tap water or industrial purified water, and the water-to-material ratio (water / composite solid waste coagulant) is 0.50.

[0184] A method for preparing a lightweight aggregate foamed geopolymer wall material, which differs from Example 1, except that the carbonization curing time is changed to 5.5h.

[0185] Carbon footprint assessment of the above-mentioned lightweight aggregate foamed geopolymer wall material: Net carbon footprint -11.5 kg CO2 / m³ 3 .

[0186] Performance test results: 28-day compressive strength 4.0 MPa; thermal conductivity 0.148 W / (m·K); bulk density 540 kg / m³ 3 Carbon fixation rate 12.3%; cost reduction 5.9%; shrinkage rate 0.27%.

[0187] Example 3

[0188] A lightweight aggregate foamed geopolymer wall material includes composite solid waste cementitious material, solid waste-based porous lightweight aggregate, composite alkali activator, foaming agent, foam stabilizer and water;

[0189] The composite solid waste cementitious material, by weight, includes: 55 parts fly ash, 28 parts blast furnace slag and 17 parts magnesia metallurgical slag;

[0190] The particle size of the solid waste-based porous lightweight aggregate is 3mm, and the dosage is 20% of the mass of the composite solid waste cementitious material.

[0191] The alkalinity coefficient of the composite alkali activator is 1.6, and the dosage is 13% of the mass of the composite solid waste coagulant.

[0192] The amount of hydrogen peroxide added, with a foaming agent concentration of 27.5%, is 3.2% of the mass of the composite solid waste gelling agent.

[0193] The dosage of the foam stabilizer sodium dodecyl sulfate (SDS) is 0.4% of the mass of the composite solid waste coagulant;

[0194] The water is tap water or industrial purified water, and the water-to-material ratio (water / composite solid waste coagulant) is 0.60.

[0195] A method for preparing a lightweight aggregate foamed geopolymer wall material, which differs from Example 1, except that the carbonization curing time is changed to 9 hours.

[0196] Carbon footprint assessment of the above-mentioned lightweight aggregate foamed geopolymer wall material: Net carbon footprint -14.1 kg CO2 / m³ 3 .

[0197] Performance test results: 28-day compressive strength 3.7 MPa; thermal conductivity 0.136 W / (m·K); bulk density 510 kg / m³ 3 Carbon fixation rate 14.5%; cost reduction 5.7%; shrinkage rate 0.29%.

Claims

1. A method for preparing a lightweight aggregate foamed geopolymer wall material, characterized in that, The steps are as follows: S1: Grind fly ash, blast furnace slag, and magnesia metallurgical slag separately to a specific surface area of ​​420~550m². 2 / kg, take 35~55 parts fly ash, 25~40 parts blast furnace slag and 12~25 parts magnesia metallurgical slag and mix them evenly to obtain composite solid waste cementitious material; the solid waste-based porous lightweight aggregate is subjected to surface etching, cleaning, drying and pre-wetting treatment. S2: Mix liquid water glass, solid sodium hydroxide, and water evenly, and let stand to obtain a composite activating solution; add the remaining water to the composite solid waste coagulant and premix at low speed, then add the composite activating solution and activate and stir at high speed, then add the pretreated solid waste-based porous lightweight aggregate and disperse at medium speed, then add the foam stabilizer and continue stirring at medium speed, and finally slowly add the foaming agent and stir at low speed to foam, controlling the density of the foamed slurry to be 600~1100 kg / m³. 3 ; The composite solid waste-based porous lightweight aggregate is added at a concentration of 18-28% of the mass of the composite solid waste cementitious material; the composite activating liquid is added at a concentration of 9-14% of the mass of the composite solid waste cementitious material; the foaming agent is hydrogen peroxide with a mass concentration of 27.5%, and the amount added is 1.8-3.6% of the mass of the composite solid waste cementitious material; the foam stabilizer is sodium dodecyl sulfate, and the amount added is 0.15-0.45% of the mass of the composite solid waste cementitious material; the water-to-material ratio is 0.48-0.

62. S3: Inject the foamed composite slurry obtained in step S2 into a mold, and after low-frequency vibration treatment, let it stand at room temperature for 2.5~3.5 hours to foam. S4: Place the molded blank in an environment with a temperature of 45~55℃ and a relative humidity of ≥92% for 14~22 hours; S5: Foaming-carbonization coupled carbonization curing: Place the demolded green body in a sealed carbonization curing box and cure it for 4-10 hours under the conditions of CO2 concentration of 15~22 vol%, temperature of 30~42℃ and relative humidity of 65~78%. S6: Natural curing: The carbonized and cured green body is placed in a normal temperature natural environment for 28 days to obtain lightweight aggregate foamed geopolymer wall material.

2. A method for preparing a lightweight aggregate foamed geopolymer wall material, characterized in that, The steps are as follows: S1: Grind fly ash, blast furnace slag, and magnesia metallurgical slag separately to a specific surface area of ​​420~550m². 2 / kg; Take 35-55 parts of fly ash, 25-40 parts of blast furnace slag, 7-15 parts of magnesia metallurgical slag, and 5-10 parts of heterogeneous auxiliary solid waste and mix them evenly; or take 35-55 parts of fly ash, 20-30 parts of blast furnace slag, 12-25 parts of magnesia metallurgical slag, and 5-10 parts of heterogeneous auxiliary solid waste and mix them evenly; or take 30-45 parts of fly ash, 25-40 parts of blast furnace slag, 12-25 parts of magnesia metallurgical slag, and 5-10 parts of heterogeneous auxiliary solid waste and mix them evenly to obtain composite solid waste cementitious material; perform surface etching, cleaning, drying, and pre-wetting treatment on the solid waste-based porous lightweight aggregate. The heterogeneous auxiliary solid waste is selected from any one of steel slag powder, red mud, and recycled silica-alumina powder from construction waste. S2: Mix liquid water glass, solid sodium hydroxide, and water evenly, and let stand to obtain a composite activating solution; add the remaining water to the composite solid waste coagulant and premix at low speed, then add the composite activating solution and activate and stir at high speed, then add the pretreated solid waste-based porous lightweight aggregate and disperse at medium speed, then add the foam stabilizer and continue stirring at medium speed, and finally slowly add the foaming agent and stir at low speed to foam, controlling the density of the foamed slurry to be 600~1100 kg / m³. 3 ; The composite solid waste-based porous lightweight aggregate is added at a concentration of 18-28% of the mass of the composite solid waste cementitious material; the composite activating liquid is added at a concentration of 9-14% of the mass of the composite solid waste cementitious material; the foaming agent is hydrogen peroxide with a mass concentration of 27.5%, and the amount added is 1.8-3.6% of the mass of the composite solid waste cementitious material; the foam stabilizer is sodium dodecyl sulfate, and the amount added is 0.15-0.45% of the mass of the composite solid waste cementitious material; the water-to-material ratio is 0.48-0.

62. S3: Inject the foamed composite slurry obtained in step S2 into a mold, and after low-frequency vibration treatment, let it stand at room temperature for 2.5~3.5 hours to foam. S4: Place the molded blank in an environment with a temperature of 45~55℃ and a relative humidity of ≥92% for 14~22 hours; S5: Foaming-carbonization coupled carbonization curing: Place the demolded green body in a sealed carbonization curing box and cure it for 4-10 hours under the conditions of CO2 concentration of 15~22 vol%, temperature of 30~42℃ and relative humidity of 65~78%. S6: Natural curing: The carbonized and cured green body is placed in a normal temperature natural environment for 28 days to obtain lightweight aggregate foamed geopolymer wall material.

3. The method for preparing the lightweight aggregate foamed geopolymer wall material according to claim 1 or 2, characterized in that, In step S1, the solid waste-based porous lightweight aggregate is prepared by molding and non-firing curing from recycled construction waste powder, slag, and a small amount of fly ash. Its particle size is 3~6mm, compressive strength is ≥1.8MPa, and water absorption is ≤15%.

4. The method for preparing the lightweight aggregate foamed geopolymer wall material according to claim 1 or 2, characterized in that, In step S1, the surface etching is mechanical etching with an etching depth of 0.2~0.5mm; the drying temperature is 80~100℃ and the drying time is 2~3h; the pre-wetting treatment is performed until the moisture content of the lightweight aggregate is 5~8%.

5. The method for preparing the lightweight aggregate foamed geopolymer wall material according to claim 1 or 2, characterized in that, The alkalinity coefficient of the composite activating solution, i.e., the SiO2 / Na2O molar ratio, is 1.1~1.7; the modulus of the liquid water glass is 2.2~2.

6.

6. The method for preparing the lightweight aggregate foamed geopolymer wall material according to claim 1 or 2, characterized in that, In step S2, the stirring rate during the preparation of the composite activation solution is 300~500 r / min, the stirring time is 2~5 min, and the settling time is 6~12 min; the premixing stirring rate is 100~200 r / min, and the time is 1~2 min. The high-speed activation stirring rate is 900~1100 r / min, and the time is 4~7 min. The strong shearing action synergistically destroys the aluminosilicate network with alkali activation to generate an active aluminosilicate gel phase. The medium-speed stirring rate is 450~600 r / min, and the time is 2~3 min. The hydroxyl groups on the aggregate surface undergo a condensation reaction with the matrix gel to form a stable chemical bonding interface. The medium-speed stirring time after adding the foam stabilizer is 1~3 min; the low-speed foaming stirring rate is 120~180 r / min, and the time is 0.8~1.8 min.

7. The method for preparing the lightweight aggregate foamed geopolymer wall material according to claim 1 or 2, characterized in that, In step S3, the frequency of the low-frequency vibration is 20~30Hz, the vibration time is 15~25s, and the ambient temperature is 20±5℃.

8. A lightweight aggregate foamed geopolymer wall material prepared by a method for preparing lightweight aggregate foamed geopolymer wall material as described in any one of claims 3 to 7.

9. The application of the lightweight aggregate foamed geopolymer wall material according to claim 8 in prefabricated lightweight wall panels, thermal insulation partitions, roof insulation layers or non-load-bearing infill walls.

10. A method for evaluating the life-cycle carbon footprint of the lightweight aggregate foamed geopolymer wall material of claim 8, characterized in that, include: Define the boundaries of the full life cycle assessment, build a carbon emission factor database, calculate carbon emissions in stages, calculate net carbon footprint, and optimize raw material ratios and process parameters in reverse; In carbon footprint assessment, the functional unit is 1m. 3 Wall materials assessment covers the entire lifecycle, including raw materials, preparation, transportation, construction, service, and waste recycling.